Comparative Analysis of the Quality of White Wine Prepared with Commercial Wine Yeast and Isolated Yeast Strain from Indigenous Murcha - Sharma, Sanjog; Sangroula, Ganga; Karki, Tika Bahadur (Universitas Ahmad Dahlan, 2025)
Nepal, has a long tradition of fermenting indigenous alcoholic beverages. However, its potential in winemaking remains undiscovered, Nepal’s researcher growing interest in viticulture and wine production. This study goal to compare the quality of white wine produced using commercial yeast (CY) and yeast strains (SY1 and SY2) isolated from indigenous murcha, a traditional Himalayan starter culture. Altogether 12 yeast strains were isolated. Screening of fermentative yeast were performed on the basis of effervescence of carbon-dioxide gas in Durham’s tube, flavor, turbidity and surface growth in YM broth containing 1.8% sugar. Strain Y1 and Y7 were selected on WYDM media. Strains Y1, Y2 and commercial wine yeast were used as starter culture in wine fermentation. The grape juice (15.4 °Bx) was fermented for 12 days at room temperature. The biochemical characteristics, antioxidant activity, total phenolic content and the sensory analysis of wine were conducted. The methodology involving isolating yeast from murcha, screening fermentative strains, and wine fermentation. Statistical analysis suggested that alcohol content, ester content and total phenolic compounds were significantly different from each other in all wine samples SY1, SY2, CY (p<0.05). Results indicated that SY1 and SY2 exhibited higher fermentation activity, producing wines with significantly (p<0.05) better alcohol content (7.33–7.51% v/v), lower residual sugar (1.27–1.38), and enhanced phenolic and antioxidant properties compared to CY (7.08% alcohol, 1.45% residual sugar). Sensory evaluation ranked SY2 highest in overall acceptability. Encouraging Nepalese winemakers to adopt and apply murcha-derived yeast strains (SY2) to enhance fermentation efficiency and develop unique regional wine profiles.